2003
DOI: 10.1007/s00423-003-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Anterior partial fundoplication for gastroesophageal reflux disease

Abstract: Anterior partial fundoplication achieves effective medium- and long-term control of reflux symptoms. Technically easy to perform and associated with few complications, the procedure is superior to fundoplication with respect to the development of postoperative dysphagia and therefore represents a viable alternative to fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Both procedures achieved equivalent control of reflux and had a similar incidence of late dysphagia, but posterior fundoplication was associated with significantly less postprandial fullness and flatulence at late follow-up. One study evaluated the 6-44-month outcome of laparoscopic anterior partial fundoplication 17 . The results also suggested that the incidence of dysphagia was less than that after Nissen fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…Both procedures achieved equivalent control of reflux and had a similar incidence of late dysphagia, but posterior fundoplication was associated with significantly less postprandial fullness and flatulence at late follow-up. One study evaluated the 6-44-month outcome of laparoscopic anterior partial fundoplication 17 . The results also suggested that the incidence of dysphagia was less than that after Nissen fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…15 Kneist et al, recorded a conversion rate (1.3%). 16 In present study mean operative time in group I was 95 minutes and 116 minutes in group II. There was significant difference between both groups as regards the operative time in favor of partial anterior wrap.…”
Section: Discussionmentioning
confidence: 45%
“…17,18 Kneist et al, reported mean operative time 90 min for partial anterior fundoplication. 16 Peters et al, recorded 202±58 min for Nissen fundoplication. 19 After 3, 6, 12months, a standardized score was used to assess the clinical improvement of the symptoms after operations (heartburn and regurgitation) and revealed that both partial anterior and Nissen fundoplication are effective in controlling heartburn and regurgitation with significant difference between both groups after 3months in favor of Nissen, but after 6 and 12months follow up there was no significant difference between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term results after Thal fundoplication described the recurrence of reflux in patients with central nervous system disorders [4]. Recently, the laparoscopic approach was introduced in pediatric surgery and was beneficial [5][6][7][8][9][10]. Especially, laparoscopic fundoplication in severely scoliotic children could allow improved operative visibility and easier access to the hiatus in comparison with the open approach [5].…”
mentioning
confidence: 99%